HUKUMAN BAGI PELAKU ABORSI MENURUT KANON 1329 DAN KANON 1398 - Batlayeri, Hilarius (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2015)
The practice of abortion has a very ruinous impact for the woman in question, both physically and psychologically. Physically, abortion may cause serious damage to one’s health, even cause death. Psychologically, it may result in mental stress. According to the doctrine of the Catholic Church, abortion is a very grave misdemeanour, a sin, a transgression of God’s low. Anyone who commits abortion, automatically is penalized as is dictated in the Book of Canon Low 1983, can. 1329 and 1398. Those who effectively perform abortion, are automatically excommunicated, but those who remorsefully confess their wrongdoing, will always be welcomed back into the Church.